Narusheniya menstrual'nogo tsikla u podrostkovi molodykh zhenshchin s ozhireniem (Ожирение и метаболизм, 2010)
Obesity plays a key role in reproductive disorders. Xenical administration results in recovery of menstrual function in 78.9% and ovulation in 26.3% of patients with obesity. Hormone therapy in patients with obesity should be accompanied with Xenical therapy, which has a favorable impact on further body weight reduction (13.95% from baseline) and improvement (or stability) of metabolic parameters.